Dukungan Sosial Orang Tua dan Eksplorasi Karir dengan Pengambilan Keputusan Karir pada Pengangguran di Usia Emerging Adulthood - Karunia Wahyu Putri Sejati; Suyanti Suyanti (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aimed to determine the relationship between parental social support and career exploration with career decision-making among unemployed young adults. Early adulthood, particularly between the ages of 18 and 25, is a crucial developmental period as individuals are required to become independent, build their identity, and determine their career direction. During this phase, many individuals face challenges such as career uncertainty and unemployment, making parental social support and career exploration skills important factors that can influence the quality of career decision-making. The subjects were job seekers aged 18 and 25, categorized as young adults. The sampling technique used probability sampling. The research instrument consisted of three scales: the career decision-making scale (29 items; α = 0.903), the parental social support scale (15 items; α = 0.893), and the career exploration scale (13 items; α = 0.921). Data analysis was performed using the Pearson correlation test to test the hypothesis, and reliability was measured using the Spearman-Brown method. The results of this study indicate a significant positive relationship between parental social support and career exploration with career decision-making among unemployed young adults. This finding indicates that the higher the social support provided by parents and the more active individuals are in exploring their career options, the better their ability to make appropriate career decisions. The implications of this study emphasize the importance of parental involvement in supporting children during the transition to the workforce and emphasize the need for intervention programs that systematically encourage career exploration among unemployed young adults. This is expected to enable individuals to develop more mature career decision-making capacities and thus be able to face the challenges of job uncertainty in the modern era.